Metastasis of Dermatofibrosarcoma from the Abdominal Wall to the Thyroid Gland: Case Report - Alexander Kreze; Andrea Zápotocká; Tomáš Urbanec; Jiří Koskuba; Mikuláš Pura; Pavel Vítek; Pavol Praženica; Eva Traboulsi (Case Reports in Medicine)
Metastases in the thyroid gland are very rare. Even the rarer are sarcoma metastases. A 52-year-old woman was referred to our department for evaluation of a nodule in the right lobe of the thyroid gland. She had a history dermatosarcoma of the abdominal wall with known metastasis in the lung. Clinically she had neck pain and worsened swallowing. Objective assessment (ultrasound, computed tomography, and magnetic resonance) indicated a voluminous right lobe nodule with mechanical syndrome, and a fine-needle aspiration biopsy revealed a very suspicious malignant finding. After surgery, the diagnosis was metastasis of dermatofibrosarcoma protuberans. Subsequent treatment was radio- and chemotherapy.